2016
DOI: 10.3354/meps11534
|View full text |Cite
|
Sign up to set email alerts
|

Potential influence of offshore oil and gas platforms on the feeding ecology of fish assemblages in the North Sea

Abstract: This article presents results from the first detailed study on the feeding habits of fish assemblages associated with offshore oil and gas platforms in the North Sea. Multi-seasonal sampling was conducted at one of the oil platforms located in the central North Sea between September 2010 and January 2014 to characterise temporal variation in the stomach contents of different fish species. A total of 6 fish species were recorded, including commercially important gadoids such as saithe Pollachius virens, haddock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…The faunal assemblage supported by the hydroid turf potentially provide a food source for the fishes observed at the site. This is supported by the fact that the organisms recorded in the hydroid turf in this study are equivalent to the polychaete worms, peracarid crustaceans and anomuran and brachyuran crabs that characterized the stomach contents of fish examined in a study of the feeding ecology around the Miller platform in the northern North Sea (Fujii, 2016).…”
Section: Discussionsupporting
confidence: 55%
“…The faunal assemblage supported by the hydroid turf potentially provide a food source for the fishes observed at the site. This is supported by the fact that the organisms recorded in the hydroid turf in this study are equivalent to the polychaete worms, peracarid crustaceans and anomuran and brachyuran crabs that characterized the stomach contents of fish examined in a study of the feeding ecology around the Miller platform in the northern North Sea (Fujii, 2016).…”
Section: Discussionsupporting
confidence: 55%
“…Anthropogenic marine structures can act as artificial reefs that locally increase fish biodiversity and biomass (Pickering & Whitmarsh, 1997;Langhamer, 2012). This has proven to be the case also for O&G installations operating at ,100 m depth in the North Sea, where installations attract and concentrate a wide range of fish species (Soldal et al, 2002;Fujii, 2015Fujii, , 2016. These include, for example, cod (Gadus morhua), haddock (Melanogrammus aeglefinus), saithe (Pollachius virens), sand eel (Ammodytes spp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, aquaculture cage sites have proven to have attractive or repulsive effects on various fishes and shellfish, however, the long term and ecosystem-wide consequences are still not fully understood (Callier et al 2017). Offshore oil and gas platforms are also known to attract marine life (Fujii 2016) and along with sea cage sites are increasing worldwide (Dafforn et al 2015, Gentry et al 2016. Although this trend of ocean exploitation is widely understood to be detrimental to marine biodiversity, there is some promise in these structures being decommissioned strategically and acting as productive artificial habitat.…”
Section: Research Applications and Conclusionmentioning
confidence: 99%
“…Although this trend of ocean exploitation is widely understood to be detrimental to marine biodiversity, there is some promise in these structures being decommissioned strategically and acting as productive artificial habitat. Several studies (including Smith et al 2016) have shown that artificial reefs can harbor similar biodiversity and abundance as natural systems, and many decommissioned offshore energy platforms may act as localized marine protected areas, either through maritime legislation preventing activity in the area or through difficulty of adapting commercial fishing techniques such as trawl nets to these contexts (Fujii 2016). Therefore, strategically designed FADs that are not open-access can act as useful research platforms to develop new monitoring approaches while maintaining the integrity of the study population, and enhance our understanding of how anthropogenic marine usage is affecting biodiversity.…”
Section: Research Applications and Conclusionmentioning
confidence: 99%